Artificial modifications lead to the formation of persistent bare patches in saltmarshes - Wang, Qing; Shao, Dongdong; Cui, Baoshan; Ren, Ze; Ning, Zhonghua; Gao, Fang; Wang, Andong (Frontiers in Marine Science, 2022)
Human activities have profoundly affected coastal wetlands. Apart from direct occupation, indirect influences are usually caused by modifications to environmental conditions, which are various and complex. Saltmarsh bare patches might be related to these artificial modifications. They have little or no vegetation cover and lose some important functions. Hence, the mechanisms underlying saltmarsh bare patches and the effects of artificial modifications should be studied. We took the Yellow River Delta as our research object and explored the characteristics of saltmarsh bare patches in the Yellow River Estuary Natural Reserve. Our results show that artificial modifications limit some key plant life stages and thus hinder the natural regeneration process. Once suffering from fatal events, such as long-term inundation or artificial damage, this limitation will lead to the formation of persistent bare patches in saltmarshes. First, a shortage of local seed sources will be induced by the death of local plants when they are affected by a fatal event. Second, the replenishment of external seeds is often constrained by dikes and dams. Third, construction activities and the prolonged high-water inundation events can lead to soil compaction and the lack of microtopographic heterogeneity, which will hinder the retention and anchorage of seeds. Overall, it is essential to realize the underlying mechanisms of persistent bare patches and their potential to be included in cost-effective restoration or management plans.